Mediation Success Rate at the Karangasem Regency Employment Service - Yowana, I Made Adiwidya; Suputra, Kadek Dwiatmika Benny (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The purpose of this study is to examine the level of mediation success at the Karangasem Regency Manpower Office. The selection of the research location was chosen deliberately, on the grounds that Karangasem Regency currently has quite good tourism development in Bali. So that it has an impact on the absorption of labor in the tourism sector. To answer the research objectives, the respondents determined were mediators at the Karangasem Regency Manpower Office and labor law practitioners. The data were analyzed using qualitative analysis, namely the data and facts found would be described. Furthermore, it will be reviewed based on existing references or based on logic. The results of the study showed that out of 13 industrial relations disputes, 11 of them were successfully reconciled. Only two disputes failed in mediation. So that the percentage of mediation success reached 84.62%. The fairly high level of success is driven by several factors, namely: compliance with mediation procedures by stakeholders; a massive and intense approach by the mediator to the parties; an approach from the mediator which is also carried out informally or outside the mediation schedule; and an explanation by the mediator to the parties regarding the benefits of peace.